Changing The Trends Of Agricultural Activity (Vegetarian) In The Wasit Area Of The Duration (2008-2018) - سهم رسن, ناجي; عبد كاظم الوائلي, نجم (Journal of College of Education, 2020)
The researcher has taken a change in the directionsof agricultural (plant) activity in wasit governorate for a period of (2008-2018) a scientific problem for the purpose of the study,The purpose of the repentance of the nature of the changes in plant crops in the cultivated areas, Production and productivity, And determine the trends of these changes, Whether positive or agricultural development in wasit governorate, Through the study showing an increase in real estate estate areas, The increase is due to the reclamation projects undertaken by the concerned authorities in wasit governorate during the period (2008-2018) offset by a smaller percentage increase in the cultivated areas,  This increase was only limited to the areas of wheat and wheat crops while the cultivated spaces of plant crops and the other saw a clear decline in the same period as well as the disappearance of other plant crops, especially in the year (2018) of the most important sheikh, cotton, white, white, solid and paint. However, on the other hand, most of these plant crops witnessed an increase in production and productivity as a result of the use of fertilizers and modern techniques in agricultural production, Thus, it turns out that agricultural development in wasit governorate is still below the required level, Which requires the concerned authorities to increase government supprt for farmers and improve the performance of irrigation and drainage progects and other measures that would increase the areas planted with various plant crops.
Keywords: Absolute Change, Relative Change, Relative Measurement Equation, Arable Land, Really Cultivated Land, Wasit Governorate